Analisis Kuantitatif Eksploitasi Akun Google Pasca Phishing Berbasis Konsistensi Jaringan - Muhammad Syahrul Haq; Heribertus Yulianton (JITU, 2026)
Phishing attacks experienced a significant increase during the COVID-19 pandemic, with over 160,000 phishing domains identified quarterly in 2020. This research analyzes login success using phishing-derived data through residential proxies to identify critical factors affecting attack effectiveness against Google authentication systems. Quantitative methodology with controlled experiments utilized 150 Gmail accounts created specifically for this research, with a maximum of 15 login attempts per account. Results demonstrate a 90.7% success rate (136 of 150 cases), with three dominant factors: IP address accuracy (100% match = 97.8% success rate), tier-1 Malaysia ISP/ASN matching (AS4818 DiGi 92.3%, AS9534 Maxis 91.9%, AS4788 TM 90.3%), and geographic location consistency (Kuala Lumpur 59.3% with 91% success rate). Critical findings reveal systemic vulnerabilities in Google's 7-day old password validity policy, creating a window of vulnerability where 22.1% of attacks succeeded on days 3-6 post-password change. This research contributes to cybersecurity literature by providing a quantitative framework for measuring residential proxy effectiveness in post-phishing exploitation and recommending mandatory 2FA implementation and reduction of old password validity period to maximum 48 hours.